Archery’s-ID Instructional Design Model: Promoting Ethical Development and Academic Performance to Support Sustainable Education Goals - Eri Wahyudi; Darmansayh; Ridwan; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2026)
This study addresses low moral understanding, ethics, and academic performance among sixth-grade students at SD Negeri 12 Padanglua, manifested in behaviors such as cheating and lack of responsibility. Conventional teaching methods have proven ineffective in fostering these values. This research investigates the impact of the Archery’s ID Model on students' moral, ethical, and mathematics learning performance. Using a quasi-experimental design with a Nonequivalent Control Group, the study involved 60 students (30 in the experimental class and 30 in the control class). Data were collected through pretests and posttests and analyzed using the Independent T-Test. The results indicate that the Archery’s ID Model significantly outperformed conventional methods. The experimental group achieved higher average scores in moral understanding (86.4), ethics (84.2), and learning performance (85.5) compared to the control group (72.1, 70.5, and 72.3, respectively). Statistical analysis confirmed significant improvements across all variables (p < 0.001). These findings suggest that the Archery’s ID Model is an effective tool for enhancing both character values and academic outcomes in mathematics.